The Idea of Customary Law Community Representation in the Regional Representative Council - Iwan Erar Joesoef (Unnes Law Journal, 2020)
The Customary Law Community (Masyarakat Hukum Adat, MHA) as part of the Customary Law System is recognized for its existence and its implementation in the National Land Law (Hukum Tanah Nasional, HTN). In the Explanation of the Basic Agrarian Law (UUPA) it is stated that the function of Customary Law as the main source in the development of HTN, although such recognition is accompanied by conditions as long as in reality they still exist and in accordance with national and state interests. This paper analyses and examines the problems of MHA in the concept of regional representative council. The problem on this paper come up from various problems concerning to ulayat land and its conflict between indigenous people and government. The research emphasized that the main problem is the inequality of perception between the Executive, Judiciary and Legislative institutions in the consistency of compensation payments resulting in the re-claim of Tanah Ulayat (Adat), there is no basis for a multi-dimensional approach (anthropology, sociology and others besides the juridical approach). This means that the formal juridical approach alone does not achieve effective results. The question is whether the constitutional MHA can have representation in the Regional Representative Council (DPD) and what forms of democracy are appropriate and can channel the aspirations of the MHA.